Blue Carbon and Food Security: A Systematic Review of Mangrove Ecosystem Services for SDG 13 (Climate Action) and SDG 2 (Zero Hunger) - Sungkawati, Endang; Umali, Jamal (CV. Bimbingan Belajar Assyfa, 2024)
Mangroves play a dual important role in sustainable development, serving as blue carbon storage and supporting food security through fisheries support. Research on the contribution of mangroves to climate change mitigation and food security is increasingly relevant in the pursuit of Sustainable Development Goals (SDG) 13 (Climate Action) and SDG 2 (Zero Hunger). This study aims to synthesize the latest research results from 2022–2025 related to mangrove ecosystem services, particularly in supporting carbon sequestration and fisheries productivity. The method used is a systematic review of relevant national and international scientific publications during that period. The results of the study show that mangrove conservation and restoration significantly enhance carbon sequestration capacity in coastal areas while improving fish catches. This contributes to the reduction of greenhouse gas emissions and increases the income and food availability of coastal communities. However, policy integration linking climate and food agendas remains limited and requires further attention. In conclusion, integrated mangrove management will strengthen the contribution of mangroves to achieving SDG 13 and SDG 2, necessitating synergy between sectors in formulating policies based on scientific evidence.